Perception and Evaluation of the Effectiveness of a Mobile Application for an Educational Arabic Charade Game in Acquiring Arabic Skills - Md. Noor, Mohamad Lukman Al Hakim; Abdul Gani, Muhamad Zamri Bin; Ismail, Nur Shuhadak Binti; Ahmad, Nor Zahidah Binti; Mohd, Khairun Nisaa; Md. Ghalib, Mohd Feham Bin; Abdul Aziz, Nur Farhana Binti (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
This study investigates students' perception of the effectiveness of an edutainment instructional module, specifically the Arabic Educational Charade Game, among students in a tertiary institute. Al-Jazzar's instructional development model was utilized to compose lessons focusing on daily Arabic sentence usage. Learning Arabic vocabulary and speaking skills can be challenging for many learners, especially non-Arabic speakers. The study's objectives are to outline the procedures for designing and producing an edutainment instructional module using this model and to explore students' perception of the instruction delivery in the Arabic Charade Game for acquiring vocabulary and improving speaking skills. The study follows a developmental method with the model as the main framework. In conclusion, the study recommends using a viable instructional development model for materials development and leveraging edutainment environments to enrich students' vocabulary and improve their Arabic speaking skills.